Understanding the market potential of products from alternative food networks in a transition economy - A discrete choice experiment - Judith Möllers; Theresa Bäuml; Thomas Dufhues (British Food Journal, 2022)
Purpose: Ethical consumption is on the rise amidst concerns about the environmental and health impacts of industrial agriculture. In light of increasingly complex food choices, alternative food networks have emerged. However, their success depends on a deeper understanding of the product attributes that guide (ethical) consumer decisions. This study focuses on the preferences of consumers when choosing and buying fresh vegetables in Romania. Design/methodology/approach: This study employs a discrete choice experiment to determine how consumers make trade-offs across a set of product attributes, such as local origin and production method. Findings: The study analysis sheds light on the importance of food attributes relevant to ethical consumers. The main barrier to making an ethically driven choice is convenience. While local production remains of lower importance than the production method, the authors show that the Romanian consumers surveyed strongly prefer non-certified "traditional" vegetables over certified organic products. Originality/value: This study is pioneering with a state-of-the-art discrete choice setting looking at a set of product attributes that reflect the demand of ethical consumers in an understudied transitional context. The authors go beyond the current debate on the trade-off between organic vs local food labels by introducing traditional small-scale production as a separate attribute level. The food attribute preferences of different consumer segments and a market simulation offer relevant insights how to market fresh vegetables to health- and environmentally-conscious urban people.
Keywords: 330; Romania; consumer preference; discrete choice experiment; local origin; organic production; traditional production